Comparison of non-viral transfection methods in melanoma cell primary cultures - Micka, Bettina; Schadendorf, Dirk (Cytokine, 2002)
Melanoma primary cultures were transiently transfected via electroporation and lipofection for comparison. Transfection efficiency was superior with electroporation (58±9%) as compared to lipofection (23±9%) as determined by enhanced green fluorescent plasmid (EGFP) transfection. Secretion of IL-2 persisted for up to 3 weeks after electroporation. The increase in sensitivity against immunologic effector cells by transfection with IL-2 was not significant. Our results show the feasibility of a gene tranfer into primary human melanoma cells, different from retroviral transduction.
Available online 25 May 2002
Gesehen am 26.02.2019